The Effect of Group Play Therapy on Anxiety in Children Diagnosed with Leukemia - Elham Momeni Gazestan; Alireza Heydari; Behnam Makvandi; Fardin Moradimanesh (Zanjan University of Medical Sciences and Health Services, 2021)
Background: One of the factors leading to anxiety in children with cancer is child hospitalization. This anxiety can be due to separation, sadness, as well as fear of a new environment, disability, and continuation of life. Objectives: The present study aimed to evaluate the effectiveness of group play therapy on anxiety in children with leukemia. Methods: The current research had an applied and quasi-experimental approach, with a pretest-posttest design and a control group. The statistical population of this study included all 8-12-year-old children with leukemia hospitalized in Dr. Afzalipour Hospital in Kerman in 2018. Among them, 30 children were selected by a convenient sampling method and were randomly assigned to the two experimental and control groups equally. The research tool was the Multidimensional Anxiety Scale for Children (MASC). Concerning the inferential analysis, the analysis of covariance (ANCOVA) method was used to compare quantitative variables between the three groups. Also, the ANCOVA model was used for modeling the difference between pretest and posttest measurements and adjusting for the effect of confounding variables such as gender and age. The analyses were performed using SPSS.22 software. Results: The results showed a significant reduction in anxiety scores between children who received group play therapy (mean anxiety=59.60) and those who did not receive any intervention (mean anxiety=60.60) (p>0.001). Based on the findings, the group play therapy intervention is effective in anxiety in children with leukemia. Conclusion: According to the findings of the present study, it can be concluded that group play therapy is effective in reducing anxiety in children with leukemia.